Wahdatul Ulum Integrated Pedagogical Competence: Analysis in Pre-service Biology Teacher - Indayana Febriani Tanjung; Nirwana Anas; Miza Nina Adlini (Postgraduate, University of Mataram, 2023)
This study aims to know the integrated pedagogical competence of wahdatul ulum in pre-service biology teacher. The measured pedagogical competence indicators focused on the design and implementation of learning. It can be seen from the ability of students to develop wahdatul ulum-based learning scenarios and its implementation. This study used a descriptive qualitative research method using learning scenario assessment sheet and observation sheet on the implementation of learning scenarios as data collection instruments. Participants were 4th semester of biology education students who take biology learning strategy courses. 12 participants were selected by purposive sampling. The data obtained were then analyzed descriptively. The results showed that pre-service biology teacher students were able to create an excellent learning scenario covering aspects of the completeness of the learning scenario components, the suitability of the subject name, the selection of learning models, the formulation of learning activities, and language. The suitability of learning objectives and wahdatul ulum aspects were classified as good. There needs to be an emphasis to put the learning objectives in learning scenarios so that the learning outcomes are clear. The meaning of the verses of the Qur'an regarding the material also needs to be explained to support the integration of wahdatul ulum in learning. In the implementation of learning, each stage of the preliminary activity, core activity, and closing activity was carried out very well, according to the learning scenario that had been made. The implication of this research is that there is a need for strengthening of a comprehensive understanding in the delivery of material on learning strategies and planning for biology course